The Relationship of Pressure Ulcers, Race, and Socioeconomic Conditions After Spinal Cord Injury - Saunders, Lee L (American Paraplegia Society, 2010)
OBJECTIVE: To identify risks factors associated with pressure ulcers (PrU) after spinal cord injury (SCI) by examining race and indicators of socioeconomic status (measured by income and education). We hypothesize African Americans will have a greater risk for PrUs than whites, but this relationship will be mediated by the 2 socioeconomic status indicators. DESIGN: Cohort study. SETTING: A large rehabilitation hospital in the southeastern US. PARTICIPANTS: 1,466 white and African American adults at least 1-year post-traumatic SCI. OUTCOME MEASURES: (a) PrUs in the past year, (b) current PrU, (c) surgery to repair a PrU since injury. RESULTS: In preliminary analyses, race was significantly associated with having a current PrU and with having surgery to repair a PrU since injury. In multivariable analyses, the relationships of PrU with having a current PrU and with having surgery to repair a PrU were both mediated by income and education such that the relationships were no longer significant. Lower income was associated with increased odds of each PrU outcome. After controlling for other variables in the model, education was associated with increased odds of having a current PrU. CONCLUSION: These findings help clarify the relationships between race and socioeconomic status with PrUs after SCI. Specifically, a lack of resources, both financial and educational, is associated with worse PrU outcomes. These results can be used by both providers and policy makers when considering prevention and intervention strategies for PrUs among people with SCI.